LIGHTS. The extended point spread functions of the LIGHTS survey at the LBT - Nafise Sedighi; Zahra Sharbaf; Ignacio Trujillo; Sepideh Eskandarlou; Giulia Golini; Raúl Infante-Sainz; Samane Raji; Dennis Zaritsky; Pedram Ashofteh Ardakani; Nushkia Chamba; S. Zahra Hosseini-ShahiSavandi; Richard Donnerstein; et al. (The Open Journal of Astrophysics)
With the arrival of the next generation of ultra-deep optical imaging surveys reaching $μ_V$ $\sim$ 30 mag/arcsec$^2$ (3$σ$; 10′′ $×$ 10′′), the removal of scattered light due to the point spread function (PSF) effect remains a critical step for the scientific exploitation of the low surface brightness information contained in these data. Because virtually all pixels in the ground-based images are affected by an unwanted screen of light with a brightness greater than $μ_V$ $\sim$ 29 mag/arcsec$^2$, the characterization of the extended PSF (R $>$ 5 arcmin) is mandatory. We describe the procedure used to construct the extended PSFs of the LIGHTS survey in the g- and r-band images taken with the Large Binocular Cameras (LBCs) of the Large Binocular Telescope (LBT). We produce PSFs with a radial extension of 6.5 arcmins. These are later extended to 30 arcmins following an empirically motivated power-law extrapolation of their behaviour in their outermost regions. As an example of the application of our methodology, we subtract the scattered light around the galaxy NGC3198. The result of this subtraction clearly shows the outermost parts of the galaxy's disc, which have been obscured by the influence of nearby bright stars. We make all the PSF (compact and extended) models publicly available.